Production Function Estimates of Agro-Based Consumer Goods Industries of Tamil Nadu - Manonmani, M. and Geetha, K.T (2010)
The Production Function is analytical tool to measure the degree of Factor Substitution and Returns to Scale. A large number of empirical studies have been made to estimate Elasticity of Substitution and Returns to Scale at national level and at the industry level. The studies at the regional level are limited and not comprehensive. The state of Tamil Nadu has traditionally been an agricultural state. In recent times however, there has been a vast shift from agriculture to industry. Hence, it is worthwhile to examine the degree of factor substitution and returns to scale in the manufacturing sector specifically agro-based consumer goods industry of Tamil Nadu. This study was undertaken for the period from 1979-80 to 2004-05.Statistical tools such as CD, CES and VESproduction function estimates were applied to analyse the data. It is surprising to note that all industries excepting the manufacture of Food Products, Beverages and Tobacco were enjoying increasing returns to scale which signifies the scope for economies of scale. All the industries were found have neutral technical progress, since the co-efficient of trend factor was significant. Solow‘s decomposition showed that the increase in labour productivity was more due to the technical progres (3 out of 5 industries) than capital intensity. Only two industries, viz., the manufacture of Food Products, Beverages and Tobacco and the manufacture of Leather and Leather Products could explain unitary elasticity of substitution between labour and capital. Excepting manufacture Wood and Wood products, all the other industries supported the efficiency-wage hypothesis.